Nitric oxide production and perivascular nitration in brain after carbon monoxide poisoning in the rat. - H Ischiropoulos; M F Beers; S T Ohnishi; D Fisher; S E Garner; S R Thom (The Journal of Clinical Investigation, 1996)
Nitric oxide is a short-lived free radical and physiological mediator which has the potential to cause cytotoxicity. Studies were conducted to investigate whether nitric oxide, and the potent oxidant peroxynitrite, were generated in brain during experimental carbon monoxide (CO) poisoning in the rat. Nitric oxide production was documented by electron paramagnetic resonance spectroscopy, and found to be increased by ninefold immediately after CO poisoning. Evidence that peroxynitrite was generated was sought by looking for nitrotyrosine in the brains of CO-poisoned rats. Nitrotyrosine was found deposited in vascular walls, and also diffusely throughout the parenchyma in inummocytochemical studies. The affinity and specificity of an anti-nitrotyrosine antibody was investigated and a solid phase immunoradiochemical assay was developed to quantity nitrotyrosine in brain homogenates. A 10-fold increase in nitrotyrosine was found in the brains of CO-poisoned rats. Platelets were involved with production of nitrotyrosine in the early phase of exposure to CO. However, nitrotyrosine formation and leukocyte sequestration were not decreased in thrombocytopenic rats poisoned with CO according to the standard model. When rats were pre-treated with the nitric oxide synthase inhibitor, L-nitroarginine methyl ester, formation of both nitric oxide and nitrotyrosine in response to CO poisoning were abolished, as well as leukocyte sequestration in the microvasculature, endothelial xanthine dehydrogenase conversion to xanthine oxidase, and brain lipid peroxidation. We conclude that perivascular reactions mediated by peroxynitrite are important in the cascade of events which lead to brain oxidative stress in CO poisoning.